PENERAPAN MODEL PEMBELAJARAN TEMATIS DALAM PELAKSANAAN KURIKULUM BERBASIS KOMPETENSI DI SEKOLAH DASAR - Arini E stiastuti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2007)
Competence based curriculum entrust that leming process in the first and second class of elementarry' school applies thematic learning so the learning is more meaningful. This decision occurs from many problems faced by students of class one and two of elementary school that is the high number or broken off school The thematic learning more stressed to the student participation in the learning process actively. So that can be expected the result of student learning can be optimal. In the large boundaries this research through two large step ie, the development and implementation inthe field. For the development learning model thematic inthe elementary school that used acuan4- De define, design, develop, and disseminate. The method of collecting data that used is the given test To know the data. The student achievement, observe class through the process learning cover the activity ofteacher and student, the skill of teacher inthe manage oflearning process, and affectivity o flearning with the model oflearning thematic. The complete of result learning student before applied learning model thematic yet have not been completed more than 90%. The skill of teacher in the implementation learning get 3,8 activity stu• dent in the learning process get the score 3,7. '01e affectivitylearning with the learning thematic 3,9. The implementation model learning thematic inthe elementary school success in good condition. So 11 is advised to the teachers in the second class of elementary school implement learning thematic according to the requirement oflearning process.